(untitled) (Revista Iberoamericana de Bioética, 2022)
Bioethics was born as a fundamental instrument for the protection of the rights of living beings, and covers the protection of animal welfare, not only in the field of research, but as part of the actions of the human being. Currently, animal models represent the closest thing to study physiological and pathological responses in humans, as well as testing new biological compounds. In this paper, the main animal models for the evaluation and investigation of epilepsy are compared and their ethical aspects are reflected in studies conducted by different research teams around the world.